Multi-modal analysis of oxidation on Fe-Cr-Ni austenitic stainless steel 304 exposed to beyond-design basis temperatures. (1st July 2023) - Copeland-Johnson, Trishelle M.; Nyamekye, Charles K.A.; Ecker, Lynne; Bowler, Nicola; Smith, Emily A.; Rebak, Raul B.; Gill, Simerjeet K.
Abstract: Stainless Steel 304 is being investigated for accident tolerant claddings. In this investigation, we use multi-modal characterization to evaluate oxidation under laboratory air versus 100% steam at 1200 ºC for 2 h. Air oxidation features Fe(NiMn)O4, Fe3 O4, Fe(3−x) Crx O4, and Cr2 O3 . Steam oxidation produces a dual layer, containing Fe2 O3 -enriched porous outer layer and sub-surface matrix of Fe3 O4 /Fe(3−x) Crx O4 with SiO2 /Fe(3−x) Six O4 . From these findings, we postulate the oxidation mechanism. Arrangement of oxidation products in air corroborates with anticipated diffusion behavior, except Cr2 O3. However, arrangement in steam deviates due to presumably intergranular interactions with H2 O, resulting in the sub-surface matrix. Graphical Abstract: ga1 Highlights: SS304 was exposed to air and steam at 1200 °C for 2 h. Oxidation in steam gave rise to a dual Fe-enriched surface layer. Oxidation in air gave rise to a Fe(NiMn)O4, Fe3 O4, Fe(3−x) Crx O4, and Cr2 O3 surface layer. Results on steam oxidation somewhat agree with historical data reported by Bittel, et al. and Ishida, et al.